Toxins and biologically active compounds from microalgae. - Rossini, Gian Paolo, editor (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2014)
This book provides a structured account of the existing knowledge of toxic algae, the chemistry of the toxins they produce, the effects these substances exert in humans and wildlife, as well as the strategies envisaged to protect public health and the environment. It covers recent advances in the understanding of the biology of toxin producers and the factors involved in the appearance and dynamics of harmful algae blooms, the factors affecting toxin production, the synthesis of toxins both in natural producers and by chemical means in a lab, and the toxin groups posing continuing and novel hazards to living systems.